2015
DOI: 10.18632/oncotarget.5650
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms involving gain or loss of CpG sites are significantly enriched in trait-associated SNPs

Abstract: Some single nucleotide polymorphisms (SNPs) influence the existence of CpG sites, the basis of DNA modification such as methylation and hydroxymethylation. These polymorphisms can lead to gain or loss of CpG sites and were defined as CpG site related SNPs (cgSNPs) in this study. The cgSNPs change DNA sequence and might potentially affect DNA modification such as methylation. However, the functional consequence of cgSNPs is poorly understood. We observed that a considerable proportion (23.0%) of common variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
(34 reference statements)
0
24
0
Order By: Relevance
“…Numerous studies focus on differentially methylated regions in complex diseases. The role of DNA methylation in cancer etiology and progression is well established 13 , 35 . Our EMSA results indicate that while allele G of rs4693608 is susceptible to DNA methylation, allele A may escape this modification.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies focus on differentially methylated regions in complex diseases. The role of DNA methylation in cancer etiology and progression is well established 13 , 35 . Our EMSA results indicate that while allele G of rs4693608 is susceptible to DNA methylation, allele A may escape this modification.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable proportion of the best-CADD5 meQTL-SNPs represents deleterious coding SNPs that also create/abolish CpG sites. SNPs affecting CpG sites account for up to 20% of common SNPs in human genome 39 , 40 , 53 , and were found to be significantly enriched in eQTLs and in trait-associated SNPs 53 . The potentially methylation-sensitive hippocampal QTL-SNPs might exert meaningful susceptibility effects of trait-associated SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed that the variant allele of rs9660710 is an eQTL for miR-429 expression and significantly increase the miR-429 expression in normal tissues. Moreover, rs9660710 is a CpG site related SNP (cgSNP) [36] and meQTL for miR-429 expression. Consequently, we speculated that rs9660710 may disrupt transcription factor response elements or DNA methylation to promote the expression of miR-429, respectively.…”
Section: Discussionmentioning
confidence: 99%